2008
DOI: 10.1091/mbc.e07-04-0394
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Functions for Arf Guanine Nucleotide Exchange Factors at the Golgi Complex: GBF1 and BIGs Are Required for Assembly and Maintenance of the Golgi Stack andtrans-Golgi Network, Respectively

Abstract: We examined the relative function of the two classes of guanine nucleotide exchange factors (GEFs) for ADP-ribosylation factors that regulate recruitment of coat proteins on the Golgi complex. Complementary overexpression and RNA-based knockdown approaches established that GBF1 regulates COPI recruitment on cis-Golgi compartments, whereas BIGs appear specialized for adaptor proteins on the trans-Golgi. Knockdown of GBF1 and/or COPI did not prevent export of VSVGtsO45 from the endoplasmic reticulum (ER), but ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
125
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 86 publications
8
125
0
Order By: Relevance
“…We could demonstrate that BFA can partially resemble the phenotype of Arfgef2 GT/GT mutant embryonic development. One can argue that BFA inhibits not only BIG2 but also GBF1 and BIG1, however, it has been demonstrated that overexpression of GBF1 and BIGs have opposite effects on the sensitivity to BFA (Claude et al 1999;Shinotsuka et al 2002b;Manolea et al 2008). Moreover, the phenotype of GBF1-depleted cells by using siRNA differed significantly from those observed in cells incubated with BFA (Szul et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…We could demonstrate that BFA can partially resemble the phenotype of Arfgef2 GT/GT mutant embryonic development. One can argue that BFA inhibits not only BIG2 but also GBF1 and BIG1, however, it has been demonstrated that overexpression of GBF1 and BIGs have opposite effects on the sensitivity to BFA (Claude et al 1999;Shinotsuka et al 2002b;Manolea et al 2008). Moreover, the phenotype of GBF1-depleted cells by using siRNA differed significantly from those observed in cells incubated with BFA (Szul et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The heptameric COPI complex associates with the Golgi membranes, resulting in the budding of COPI-containing vesicles, whose major function is to mediate transport of cellular proteins and cargo from the Golgi to the ER as well as the intra-Golgi transport (20). Depletion of COPI also perturbs the steady-state distribution of the Golgi enzymes (43) and thus inhibits processing of the VSV G protein and its transport to the plasma membrane (44,45). Further, we have found that depletion of COPZ1 subunit had no adverse effect on VSV G protein-mediated entry of pseudotyped HIV (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GBF1 is critical for biogenesis of the Golgi ribbon in mammalian cells 10,13,25,[54][55][56] and for recruitment of the COPI coat that mediates protein traffic at the ER-Golgi interface and of the AP-1 and GGA adaptors that function at the TGN. 10,11,13,25,57 The architecture of the Golgi differs in mammalian and Drosophila cells and the Golgi ribbon found in mammalian cells is replaced by scattered but still polarized Golgi mini-stacks in Drosophila cells.…”
Section: Discussionmentioning
confidence: 99%